2002
DOI: 10.1007/s00268-002-6433-2
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial risk profile for bone fractures in primary hyperparathyroidism

Abstract: Primary hyperparathyroidism (pHPT) is associated with an increased fracture risk, and decreased bone density thus has been considered an indication for surgery. However, many pHPT patients have a multifactorial risk profile for osteoporosis and bone fractures. The aim of the present study was to evaluate variables associated with fracture risk within the group of pHPT patients. A series of 203 consecutive patients operated for pHPT were investigated with bone mineral content and biochemical and clinical risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 36 publications
2
35
1
2
Order By: Relevance
“…Some authors suggest that BMD is increased with repletion in both sites whereas others claim that 25 OHD has no independent effect on BMD (22,23). Besides the negative effects on BMD, low vitamin D levels may contribute to profound and lengthened hypocalcaemia (hungry bone syndrome) after parathyroidectomy (20). Therefore it has generally been recommended to supplement vitamin D to normalize 25(OH) vitamin D levels, although there are so far no available data to support the premise that this would contribute to the prevention of hypocalcaemia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some authors suggest that BMD is increased with repletion in both sites whereas others claim that 25 OHD has no independent effect on BMD (22,23). Besides the negative effects on BMD, low vitamin D levels may contribute to profound and lengthened hypocalcaemia (hungry bone syndrome) after parathyroidectomy (20). Therefore it has generally been recommended to supplement vitamin D to normalize 25(OH) vitamin D levels, although there are so far no available data to support the premise that this would contribute to the prevention of hypocalcaemia.…”
Section: Discussionmentioning
confidence: 97%
“…Epidemiological studies suggests that the prevalence of hypovitaminosis D (including deficiency and insufficiency) is more prevalent in patients with PHPT than in the general population regardless of sex, age and the season (18). The reason for that co- (20). In addition to that there is an increased risk of osteoporotic fractures in patients with PHPT in case of low vitamin D levels (21).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanisms responsible for the low serum 25(OH)D level in PHPT are not completely clarified. The data obtained from several studies suggest that vitamin D status might influence the clinical and biological expression of PHTP [1,2,[4][5][6][7][8][9][10][11][12][13][14][15] and even recovery after surgical treatment [11,16,17], although some authors have not found such an association [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study of vitamin D therapy in patients with PHPT, vitamin D insufficiency is defined by a serum level of 21-29 ng/ml (52.5-72.5 nmol/l) and vitamin D deficiency by a serum 25-OHD level of %20 ng/ml (%50 nmol/l). In patients with PHPT, subnormal serum 25-OHD levels have been associated with larger parathyroid glands and parathyroid tumours, higher serum parathyroid hormone (PTH), calcium and alkaline phosphatase levels, accelerated bone turnover and a greater likelihood of abnormal bone and fractures (3,4,12,13). Whereas vitamin D repletion is routinely recommended for patients with hypovitaminosis D, there has been reluctance to restore serum 25-OHD levels to normal in PHPT due to concerns of potentially greater hypercalcaemia and hypercalciuria (3,14).…”
Section: Introductionmentioning
confidence: 99%